The Development of a New Vagus Nerve Simulation Electroceutical to Improve the Signal Attenuation in a Living Implant Environment - Jo, Daeil; Lee, Hyunung; Jang, Youlim; Oh, Paul; Kwon, Yongjin (Sensors, 2024)
An electroceutical is a medical device that uses electrical signals to control biological functions. It can be inserted into the human body as an implant and has several crucial advantages over conventional medicines for certain diseases. This research develops a new vagus nerve simulation (VNS) electroceutical through an innovative approach to overcome the communication limitations of existing devices. A phased array antenna with a better communication performance was developed and applied to the electroceutical prototype. In order to effectively respond to changes in communication signals, we developed the steering algorithm and firmware, and designed the smart communication protocol that operates at a low power that is safe for the patients. This protocol is intended to improve a communication sensitivity related to the transmission and reception distance. Based on this technical approach, the heightened effectiveness and safety of the prototype have been ascertained, with the actual clinical tests using live animals. We confirmed the signal attenuation performance to be excellent, and a smooth communication was achieved even at a distance of 7 m. The prototype showed a much wider communication range than any other existing products. Through this, it is conceivable that various problems due to space constraints can be resolved, hence presenting many benefits to the patients whose last resort to the disease is the VNS electroceutical.
Keywords: Electroceutical; Implantable pulse generator; IPG; IVNS; Medical Devices; Signal attenuation; Vagus nerve; Vagus nerve simulation; Vagus nerve simulation stimulation therapy; Algorithms; Animals; Humans; Prostheses and Implants; Signal Processing, Computer-Assisted; Vagus Nerve; Vagus Nerve Stimulation; electroceutical; implantable pulse generator; IPG; iVNS; VNS; VNS stimulation therapy